Loss of SRY‐box2 (SOX2) expression and its impact on survival of patients with oesophageal adenocarcinoma. Issue 10 (10th July 2017) - ten Kate, F. J. C.; van Olphen, S. H.; Bruno, M. J.; Wijnhoven, B. P. L.; van Lanschot, J. J. B.; Looijenga, L. H. J.; Fitzgerald, R. C.; Biermann, K.
Abstract : Background: Oesophageal adenocarcinoma (OAC) is a highly aggressive malignancy with poor survival, which is highly variable amongst patients with comparable conventional prognosticators. Therefore molecular biomarkers are urgently needed to improve the prediction of survival in these patients. SRY (sex determining region Y)‐box 2, also known as SOX2, is a transcription factor involved in embryonal development of the gastrointestinal tract as well as in carcinogenesis. The purpose of this study was to see whether SOX2 expression is associated with survival in patients with OAC. Methods: SOX2 was studied by immunohistochemistry in patients who had undergone potentially curative oesophagectomy for adenocarcinoma. Protein expression of SOX2 was evaluated using tissue microarrays from resection specimens, and results were analysed in relation to the clinical data by Cox regression analysis. SOX2 was evaluated in two independent OAC cohorts (Rotterdam cohort and a multicentre UK cohort). Results: Loss of SOX2 expression was independently predictive of adverse overall survival in the multivariable analysis, adjusted for known factors influencing survival, in both cohorts (Rotterdam cohort: hazard ratio (HR) 1·42, 95 per cent c.i. 1·07 to 1·89, P = 0·016; UK cohort: HR 1·54, 1·08 to 2·19, P = 0·017). When combined with clinicopathological staging, loss of SOX2 showed an increased effect in patients with pT1–2 tumours ( P = 0·010) and node‐negative OAC ( P = 0·038), with an incrementally adverse effect on overall survival for stage I OAC with SOX2 loss (HR 3·18, 1·18 to 8·56; P = 0·022). Conclusion: SOX2 is an independent prognostic factor for long‐term survival in OAC, especially in patients with stage I OAC. Abstract : Useful biomarker, especially for early disease